Effect of organic waste variations as materials for making MOL on the growth of pakcoy (Brassica rapa) plants - Najib, Muhammad Arjun; Nugraheni, Ika Afifah; Puspitasari, Amallia (International Journal of Health Science and Technology, 2024)
Organic waste is still a problem in the community because it can cause health, environmental and life problems. MOL (local microorganisms) is one of the alternatives to the use of organic waste that acts as plant fertilizer. The purpose of this study is to determine the influence of variations of organic waste as a material for making MOL on the growth of pakcoy plants (Brassica rapa). This study used a Group Random Design (RAK) consisting of 5 types of MOL, namely fruit waste (M1), vegetable waste (M2), banana hump (M3), mixed fruit waste, vegetables and banana hump (M4), and control (M5). Various types of MOL are analyzed for nutrient content at the end of fermentation and then applied to pakcoy plants. The observed growth parameters included plant height, number of leaves and plant root length, which was followed by statistical analysis of Anova. The observed nutrient test parameters are total nitrogen content, organic carbon, phosphorus, C/N ratio and pH level. Based on research, the nutrient content of various types of MOL has not met the test standards for organic fertilizers according to the Decree of the Minister of Agriculture of the Republic of Indonesia Number 261/KPTS/SR.310/M/4/2019. Only the M2 treatment has been in accordance with the C/N ratio of the organic fertilizer standard. For its effect on plant growth, MOL fruit waste (M1) is able to increase plant height and the number of leaves of pakcoy plants at 35 days after planting. However, the treatment of various MOL variations has not been able to affect the root length parameters. Thus, the application of MOL can be used as a liquid organic fertilizer to increase plant growth.